Inhibition of topoisomerase I shapes antitumor immunity through the induction of monocyte-derived dendritic cells. (1st November 2021) - Lee, Jeong-Mi; Shin, Kwang-Soo; Koh, Choong-Hyun; Song, Boyeong; Jeon, Insu; Park, Myung Hwan; Kim, Byung-Seok; Chung, Yeonseok; Kang, Chang-Yuil
Abstract: Understanding the rationale of combining immunotherapy and other anticancer treatment modalities is of great interest because of interpatient variability in single-agent immunotherapy. Here, we demonstrated that topoisomerase I inhibitors, a class of chemotherapeutic drugs, can alter the tumor immune landscape, corroborating their antitumor effects combined with immunotherapy. We observed that topotecan-conditioned TC-1 tumors were occupied by a vast number of monocytic cells that highly express CD11c, CD64, and costimulatory molecules responsible for the favorable changes in the tumor microenvironment. Ly6C + MHC-II + CD11c hi CD64 hi cells, referred to as topotecan-induced monocyte-derived dendritic cells (moDCs), proliferate and activate antigen-specific CD8 + T cells to levels equivalent to those of conventional DCs. Phenotypic changes in Ly6C + cells towards moDCs were similarly induced by exposure to topotecan in vitro, which was more profoundly facilitated in the presence of tumor cells. Notably, anti-M-CSFR reversed the acquisition of DC-like properties of topotecan-induced moDCs, leading to the abolition of the antitumor effect of topotecan combined with a cancer vaccine. In short, topoisomerase I inhibitors generate monocyte-derived antigen-presenting cells in tumors, which could be mediated by M-CSF-M-CSFR signaling. Highlights: The combination of Top1 inhibitors and cancer vaccine effectively suppress tumors. Top1 inhibitors induce accumulation of monocyte-derived DCs in tumors. Monocyte-derived DCs induced by topotecan prime and activate CD8 + T cells. Topotecan skews the phenotype of monocytes towards monocyte-derived DCs in vitro . Anti-M-CSFR impairs the DC property of monocyte-derived DCs induced by topotecan.